Management innovations: A double-edged sword for workplace well-being in worker cooperatives? An investigation among employees and general managers - Loose, Florence; Fabre, Claude; Bourdil-Resch, Maryline (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
The impact of management innovations (MI) on workplace well-being remains underexplored. In this study, we examine how MI influence two crucial dimensions of professional well-being - hedonic and eudaimonic - among 545 employees and 205 general managers of French worker cooperatives. We also investigate whether MI mediate the relationship between transformational leadership and employee well-being. The findings vary according to role: For employees, MI are positively linked to both dimensions of well-being, highlighting their value as essential workplace resources. For general managers, however, MI are associated with negative emotions, likely due to the additional job demands imposed by their implementation responsibilities. Finally, MI emerge as a key factor, fully mediating the relationship between transformational leadership and employees’ eudaimonic well-being.